Gigantism Treated by Pure Endoscopic Endonasal Approach in a Case of McCune-Albright Syndrome with Sphenoid Fibrous Dysplasia: A Case Report - Sharifi, Guive; Jalessi, Maryam; Sarvghadi, Farzaneh; Farhadi, Mohammad (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
McCune-Albright syndrome (MAS) is an uncommon polyostotic manifestation of fibrous dysplasia in association with at least one endocrinopathy that is mostly associated with precocious puberty and hyperpigmented skin macules named café-au-lait spots. We present an atypical manifestation of McCune-Albright syndrome in a 19-year-old man with the uncommon association of polyostotic fibrous dysplasia and gigantism in the absence of café-au-lait spots and precocious puberty. He presented with a height increase to 202 cm in the previous 3 years, which had become more progressive in the few months prior. Physical examination revealed only a mild facial asymmetry; however, a computed tomography (CT) scan discovered vast areas of voluminous bones with ground-glass density and thickening involving the craniofacial bones and skull base. Magnetic resonance imaging (MRI) found a right stalk shift of the pituitary with a 20 mm pituitary adenoma. We describe the diagnostic and endoscopic endonasal transsphenoidal approach for excision of the tumor.
Keywords: McCune-Albright syndrome; neuroendoscopy; pituitary adenoma